Mycale (Aegogropila) antiae sp. nov. (Demospongiae; Poecilosclerida; Mycalidae) from Galicia (NW Iberian Peninsula) - Urgorri, Victoriano; Díaz-Agras, Guillermo (Zootaxa, 2019)
A new species of Porifera collected at the Ría de Ferrol (NW Iberian Peninsula), Mycale (Aegogropila) antiae sp. nov., is described. The sponge is apricot-coloured with small sulphur-yellow spots, comprised of one or more conical or cylindrical massive bases, each with a single apical osculum. Long, more or less branched digitiform ramifications emerge from these bases, with one or two oscula in high position. The ectosomal skeleton consists of bundles of interwoven mycalostyles forming a triangular or polygonal tangential reticulation. The choanosomal skeleton shows longitudinal axial tracts, with fan-like feathered plurispicular bundles perpendicular to the surface of the sponge. It is characterized by presenting only mycalostyles as megascleres and three categories of palmate anisochelae as microscleres, the larger forming rosettes, microxeas in dragmata and thin raphides, ornamented at both ends by a fine spine, and grouped in numerous trichodragmata clustered in the subectosomal yellow spots.        This paper is registered in Zoobank under: http://zoobank.org/urn:lsid:zoobank.org:pub:2D668985-001B-4681-8C45-1DA0F804A7F1